Bit error rate for private mobile radio (PMR) due to lightning electromagnetic field radiation (LEMR) - Mohd. Esa, Mona Riza (2005)
The conceptual implementation to access the extend influence of lightning electromagnetic radiation (LEMR) on mobile radio communication. Binary data has been transmitted through a pair of Motorola Talkabout T5420 walkie-talkie with 14 channels and 38 eliminator codes and operates on 14 UHF Family Radio Service (FRS) Frequencies. Two types of induced interferences which are high voltage and high current experiment has been conducted in High Voltage Laboratory, Institute of High Voltage and High Current, UTM. In order to achieve the implementation mention above, a research has been conducted with the title of the project is â€œBit Error Rate for Private Mobile Radio (PMR) Due to Lightning Electromagnetic Field Radiation (LEMP)â€. The objective of the first part of the research is to determine whether the lightning could produce the error of the bit in term of bit error rate in digital communication. If there any errors, the research will continue to ascertain how much it damage or influence the data. In optical communication, in practice, a low bit error rate in the region 10-7 to 10-10 may be tolerated with pulse code modulation (PCM) transmission. Although, in wireless communication, the receiver will face much higher bit error rate due to the environment and nature phenomena such as rain drops, fogs, thunderstorm and lightning.